App-based learning for kindergarten children at home (Learning4Kids): Study protocol for cohort 2 and the school assessments - Frank Niklas; Efsun Birtwistle; Astrid Wirth; Tina Schiele; Anna Mues (BMC, 2022)
Abstract Background Children's early literacy and mathematical competencies are very important predictors for their later success in school and their educational attainment in general. However, not all children are able to develop to their full potential and some are at risk of failing to reach sufficient competence levels. The project "App-based learning for kindergarten children at home" (Learning4Kids) is designed as a longitudinal intervention study that tests the potential impact of a computer tablet-based intervention for kindergarten children and their families before school entry. Here, the focus lies on both, potential short-term and long-term influences on children's competencies development in kindergarten and school. Methods/design Learning4Kids uses a multi-method intervention approach and draws on expertise from different fields such as psychology, education, informatics, and didactics. It combines child test assessments with parental, educator, and teacher surveys and checklists, interviews as well as observations in the families to measure child competencies and their behaviour, and to assess family characteristics. The participating children and their families will be visited and assessed altogether seven times, starting in the second-last year of kindergarten until children are at the end of Grade 2. In cohort 1, 190 families participated in this project, whereas in cohort 2 another 310 families joined the Learning4Kids project. For the school assessments, standardized and curriculum-based tests will be used to assess children's mathematical and literacy competencies. In addition, cognitive and non-cognitive child abilities will be assessed. Discussion Learning4Kids offers substantive advances for the scientific fields of psychology and education, and also provides implications for policy and practice in the long term. Improving young children's learning trajectories and analysing these trajectories from kindergarten to primary school is both a social and economic imperative as it contributes to greater individual success and thus to societal prosperity.